Ebu Hanife (R.A.) ye göre İstihsanü’n-Nass [Serahsi’nin el-mebsut örneği] - Torun, Hacı Mustafa (My University, 2016)
“Ebu Hanife’ye Göre İstihsanü’n-Nass [Serahsi’nin el-Mebsut Örneği]” ismini taşıyan bu tezde Ebû Hanîfe (r.a.)’in Fıkıh Usûlü ilmindeki delil/ yöntemlerden istihsanın bir çeşidi olan istihsânü’n-nassa dair anlayışı Şemsüleimme Serahsî’nin el-Mebsût adlı eseri çerçevesinde ele alınmıştır. Konunun işlenişinde Ebû Hanife (r.a.)’in sünnete verdiği önem merkeze alınmıştır. Tez, bir giriş ve iki bölümden oluşmaktadır. Giriş bölümünde tezin konusu, kaynakları ve amacından bahsedilmiştir. Birinci bölümde istihsan kavramıyla ilgili birkaç başlık altında ön bilgiler verilmiştir. İkinci ve son bölümde ise Mebsut’ta Ebû Hanîfe (r.a.)’in istihsanü’n-nassa başvurduğu yerler örneklendirilmiş ve her örnek açıklanmıştır.

In this “Istihsan al- nass according to Abu Hanifa (r.a) [The case of Sarakhsy’s al-Mabsut]” entitled thesis, it has been discussed the cognizance of Abu Hanifa (r.a) on “istihsan al-nass”, one of the versions of istihsan including evidences and methods, in the İslamic jurisprudance, within the frame of Shams al- Aimma Sarakhsy’s work so-called “al-Mabsut”. Abu Hanifa’s all cares about sunnah have been centered in the dealing with the subject. The thesis consists of one introduction and two chapters. The subject of thesis, and its resources and purpose have all been discussed in the introduction. Preliminary informations relevant with istihsan are given under several topics in the first chapter. And in the second and last chapter, the places Abu Hanifa (r.a) referred to about “istihsan al-nass” have been exemplified and each example has been explained.